Strategi Promosi Kesehatan Melalui Program PHBS: Studi Pada Dinas Kesehatan Sarolangun Provinsi Jambi - Hamonangan, Jan Effendi; Dachi, Rahmat Alyakin; Sitorus, Mido Ester J.; Nababan, Donal; Sinaga, Taruli Rohana (Journal of Pharmaceutical and Sciences, 2025)
The purpose of this research is to explore in more depth all matters related to the Health Promotion Strategy through the PHBS Programme, namely Health Education, Disease Prevention and Health Protection. This type of research is qualitative research. Research involves in-depth interviews, document review, and direct observation. The informants in this study were the Head of Public Health, the holder of the health promotion programme and the community in Sarolangun. In this study, triangulation was employed by asking questions to informants and by examining written documents and field circumstances to validate the interview results. Processing research data with the in-depth interview method. The results showed that the health education strategy had an impact on individual behaviour, achieved through mass media, collaboration with puskesmas, doctors, and community groups. The disease prevention strategy has a positive effect on increasing community awareness and participation in disease prevention through health screening programs, immunisation, and environmental hygiene campaigns, which elicit a positive community response. The health protection strategy focuses more on providing hygiene facilities, forming health protection policies, and collaborating across sectors. However, challenges such as limited infrastructure and low community compliance need to be addressed through educational approaches, facility expansion, and stricter supervision to ensure programme sustainability and greater community impact.